A germanimidoyl chloride: synthesis, characterization and reactivity. Issue 11 (20th January 2023) - Li, Tong; Zhang, Li; He, Yuhao; Chen, Yizhen; Wang, Dongmin; Liu, Jingjing; Tan, Gengwen
Abstract : The first germanimidoyl chloride was synthesized, which could be facilely functionalised to yield a germanimine or an amide lithium salt. Abstract : The first germanimidoyl chloride M s Fluind t Bu -Ge(Cl)NMes (2, where M s Fluind t Bu is a bulky hydrindacene skeleton) was synthesized through the reaction of M s Fluind t Bu -GeCl (1 ) and mesityl azide (MesN3 ). In contrast, treatment of 1 with a less bulky azide ArN3 (Ar = 4- t BuC6 H4 ) produced a germatetrazole chloride M s Fluind t Bu -Ge(Cl)N4 Ar2 (3 ), and a salt [M s Fluind t Bu -GeN4 Ar2 ] + [BAr F 4 ] − (4 ; Ar F = 3, 5-(CF3 )2 C6 H3 ) followed by chloride abstraction with NaBAr F 4, both bearing a five-membered GeN4 ring. Functionalization of 2 with Ar′Li (Ar′ = 3, 5- t Bu2 C6 H3 ) or MeLi furnished a germanimine M s Fluind t Bu -Ge(Ar′)NMes (5 ) or an amide lithium salt M s Fluind t Bu -Ge(Me)2 -N(Mes)Li(thf) (6 ).